The Influence of Budget Participation, Work Motivation, Job Satisfaction on Managerial Performance with The Quality of Leader Member Exchange as An Intervening Variable in Manufacturing Companies - Mardani Supranata; Tiolina Evi Nausta Pardede (International Journal of Indonesian Business Review, 2026)
Purpose – This study aims to examine the effect of budget participation, work motivation, and job satisfaction on managerial performance, as well as to analyze the mediating role of Leader-Member Exchange (LMX) in explaining the relationships between these antecedent variables and managerial performance within manufacturing companies.. Methodology/approach –This research employs a quantitative approach using primary data collected through structured questionnaires. The sample consists of 260 managerial-level employees working in manufacturing companies. Data were analyzed using Structural Equation Modeling with the Partial Least Squares (SEM-PLS) technique to test both direct and mediating effects among the proposed constructs. Findings – The results show that budget participation and work motivation have a significant positive effect on managerial performance, whereas job satisfaction has no direct significant impact. LMX does not mediate the relationship between budget participation and managerial performance. However, LMX significantly mediates the effects of work motivation and job satisfaction on managerial performance, emphasizing the importance of high-quality leader–subordinate relationships in enhancing managerial performance. Novelty/value–This study enriches managerial accounting and organizational behavior literature by incorporating Leader-Member Exchange (LMX) as a mediating variable between budget participation, psychological factors, and managerial performance in manufacturing firms. The findings provide empirical evidence that LMX strengthens the effects of work motivation and job satisfaction on performance, offering practical insights for organizations to improve managerial effectiveness through enhanced leadership quality and participative management practices.